Some general issues of a system analysis of ethnic problems. Issue 1 (2nd January 2016) - Kuznetsov, Anatoly M.
Abstract : The article claims that the two established traditions of discussion of ethnic issues, both the Russian Theory of ethnos and the Western concepts of ethnicity, were not able to offer convincing scholarship results. The major reason for the existence of the current state of affairs is related to the constraints imposed by the disciplinary ( ethnographic and anthropologic ) approaches toward the development of the ethnic theories. To eliminate the identified deficiencies, it is suggested to use the ideas of the system paradigm, which defines the ethnic group as a complex formation able to reproduce itself ( autopoiesis ) by means of self-reference that is based on self-observation . In this context, a high theoretical potential is demonstrated by the Theory of Ethnos of Sergei Shirokogoroff, who in the 1920s–1930s suggested to use an interdisciplinary approach toward understanding of the issue of an ethnic diversity of humankind. Synthesis of these disciplines was implemented on the basis of ideas, which preempted a number of provisions of a system paradigm, such as ethnos as a process, which involves ethnic groups, and Psychomental Complex it is important to add as a foundation for cultural adaptation and preservation of ethnic groups. These findings demonstrate a necessity to use Shirokogoroff's theory to address the existing ethnic challenges with consideration of ethnic policies of different states.